(untitled) (Anwer Khan Modern Medical College Journal, 2014)
Over weight and obesity are recognized as recent threat which affecting both developing and developed countries. Obesity and its associated morbidities are leading cause of most noncommunicable diseases. Few recent studies have indicated the presence of increasing in over weight and obesity among children and adolescent but there is no study among adult groups. This cross sectional study was done to assess the prevalence of overweight, obesity and metabolic variables with their relation among medical students. Our result reveals that 8.6% & 1.9% male and 15% & 3.2% female are suffering from overweight and obesity (based on BMI) respectively. More females (31.3% and 65.2%) are centrally obese than males (3.5% and 34.8%) (According to Waist Hip ratio and Waist Height ratio respectively). But according to Waist circumference more males (30.7%) are obese than females (24%). There is also significant difference of male and female BP. DBP & SBP of male (79.22mmHg & 118.9 mmHg) have high normal level than female (72.71mmHg & 108.67mmHg) (P<0.001). There is no significant difference of glycaemic status and lipid profile with central obesity. Although male students have high upper level of blood pressure, female students are more obese than males (both according to BMI and central obesity). High blood pressure and obesity both acts as risk factors for the development of non communicable disease. Student’s awareness therefore should be increased to reduce central obesity & BP within normal range. DOI: http://dx.doi.org/10.3329/akmmcj.v5i1.18837 Anwer Khan Modern Medical College Journal Vol. 5, No. 1: January 2014, Pages 23-28